Developing supplementary reading material using macromedia flash for the fourth-grade students at elementary school - Fachruddin Indrakumara (Universitas Sarjanawiyata Tamansiswa, 2020)
The objectives of this study are to developing supplementary reading material and describing the effectiveness of supplementary reading material using Macromedia. Related to the purpose of the study, the research design used was classroom research and development research. The subject of the study was the fourth-grade Students of SDN Ngebel in the academic year 2017/2018. There were 21 students as the sample. In this research, supplementary reading material was used. The research adopted Brog and Gall’s model (1983) which are simplified in the three main stages, they are:(1) preliminary study, (2) development, (3) field testing. The reading materials were selected accordingly to be relevant to the topic. The ideas and sentences were well organized and clearly stated. The students were able to know more vocabulary and grammar, the students actively participated in the teaching and learning process. The used of Macromedia in teaching reading has improved student’s motivation in learning reading. The students expressed their ideas and experience in reading activities. The result of the findings showed that (1) the developed supplementary reading material affect the students’ motivation in joining the teaching-learning process. (2) Using the supplementary reading material, the students were enthusiastic and active in the reading activity. The product of this study is effective to be implemented in the real class to help the students become more excited in learning reading.